PENERJEMAHAN FRASA NOMINA DARI BAHASA INGGRIS KE DALAM BAHASA INDONESIA (PENELITIAN ANALISIS ISI PADA BUKU TRAFFIC RULES PT FREEPORT INDONESIA) - Yuna Tresna Wahyuna (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2018)
The main purpose of this study is to obtain an overall picture of translation of noun phrase. That is concerned with translation equivalence, translation procedure, translation shifts, and translation error in Traffic Rules PT Freeport Indonesia book. This study used a qualitative approach using content analysis method. The data in this study is noun phrase which focuses on the form of noun phrase pattern, there is 100 noun phrase translation to be represented the main problems of study, translation equivalence, translation procedure, translation shifts, and translation error. The findings of this study show the following. First, the translation equivalence has been found with formal equivalence and dynamic equivalence. Second, the translation procedure has been found with eight variety of procedure such as transference, literal, naturalization, expansion, reduction, couplet, modulation, cultural equivalent. Third, the translation shifts are structural shifts, unit shifts, class shifts, and intra-system shifts. Fourth, there is error translation of meaning has been found in this study.